2011
DOI: 10.1063/1.3624844
|View full text |Cite
|
Sign up to set email alerts
|

Improving the spectral response of amorphous Se photodetectors using organic semiconductors

Abstract: We demonstrate a heterojunction amorphous Se (a-Se)/organic semiconductor photodetector that extends the long wavelength spectral response of pure a-Se devices from a cutoff of about 500 nm to 1000 nm. We show that a-Se/organic interfaces behave similarly to organic/organic interfaces in terms of energy level alignments and organic exciton dissociation. Due to the large ionization potential of a-Se (5.7 eV), organic materials with similarly large ionization potentials are required for hole injection into a-Se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Organic materials are large-area compatible and previous studies have demonstrated that the stability and spectral response of a-Se detectors can be improved using organic materials such as a fullerene (C 60 )-doped polymer 7 and zinc hexadecafluoro phthalocyanine (F 16 -ZnPc) 8 , respectively. The hole blocking capabilities of organic materials in a-Se detectors have also been investigated 7 9 .…”
mentioning
confidence: 99%
“…Organic materials are large-area compatible and previous studies have demonstrated that the stability and spectral response of a-Se detectors can be improved using organic materials such as a fullerene (C 60 )-doped polymer 7 and zinc hexadecafluoro phthalocyanine (F 16 -ZnPc) 8 , respectively. The hole blocking capabilities of organic materials in a-Se detectors have also been investigated 7 9 .…”
mentioning
confidence: 99%
“…Improvements in quantum efficiency for different wavelengths is also made possible by the PI layer since this layer controls the dark current characteristics and additional organic layers may be deposited on top of PI. The additional organic layers will not significantly affect the dark current behavior of the device and different organic layer can be engineered to improve the spectral response of the detector (9).…”
Section: Recent Advances In Lateral Detector Designmentioning
confidence: 99%
“…By this method, in addition to the operation as a blocking layer, the semiconducting gallium-selenium alloy GaSe 9 would also advantageously operate as an active layer. Many optoelectronic properties and applications are under investigation by different research groups [17][18][19][20], including integration with organic semiconductors as a promising way to enhance device characteristics, since a-Se/organic interfaces behave similarly to organic/organic interfaces in terms of energy level alignments and organic exciton dissociation [21].…”
Section: Introductionmentioning
confidence: 99%